The Bag of social investment: management tool oriented social responsibility initiatives in SMES (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2013)
The study aims to analyze the Social Investment Fund (BIF) as a management mechanism for the Enterprise Social Responsibility initiatives (ESR) proposed by the in Small and Medium Enterprises (SMEs). It was developed under the guidelines of fieldwork-descriptive research, with a sample consisting of 25 subjects of Economic Development Organizations (EDO), selected intentionally and systematically. A 25-items questionnaire with dichotomous scale was applied. Some of the results are: 1- .there are several economic, political and social problems affecting companies, limiting their financial and operating expenses, as well as the resources to accomplish with ESR; 2. - most of the subjects expressed their desire to participate in their local BIF, which determines the possibility of implementing one in the future. It can be concluded that, as a strategy for resource management for SME 's, shareholders , families, communities, customers and suppliers can benefit from financial resources, replacement of capital, low interest loan and project implementation CSR that are targeted to the communities where they are located each of these organizations.
Keywords: social investment exchange; corporate social responsibility; SMES